The Life-course Approach in Assessment of Dental Health: A Cross Sectional Study among Finnish and Turkish Pre-adolescents - Cinar, Ayse Basak; Murtomaa, Heikki; Tseveenjav, Battsetseg (European Journal of Dentistry, 2008)
Objectives: Interest is growing on conceptualizing dental disease aetiology under the life-course approach. The aim of this study was to assess the association of dental caries experience with the major components of life-course approach, health- and behavioral capital, among Turkish and Finnish pre-adolescents, with different family-related characteristics, as this association has not been explored yet.Methods: A cross-sectional study of Finnish (n=338) and Turkish (n=611) pre-adolescents was undertaken with questionnaires and oral health data.Results: Turkish pre-adolescents, more dentally diseased (84%) than the Finnish (33%) (P<.01), had lower means of health (body height-weight) and behavioural (self-esteem, tooth-brushing self-efficacy) capital, (P<.01). Finnish pre-adolescents were less likely to live in two-parent families (P=.001) and spent less time with their mothers (P<.05). Turkish pre-adolescents with high levels of self-esteem were more likely to spend time with their mothers and less likely to live in families with three or more children (28%) than were their counterparts with low levels of self-esteem (41%). Such associations were not evident among Finnish pre-adolescents (P>.05). Health capital, in terms of body height, and family-related characteristics in differing patterns, contributed to DMFT, in common, among Turkish and Finnish pre-adolescents. Self-esteem, behavioural capital was explanatory variable for DMFT only for the Turks.Conclusions: Dental health of pre-adolescents was associated with health- and behavioural capital in different pathways under the influence of family-related characteristics. The cooperation of paediatricians and dentists is vital in assessment of general and dental health in a holistic context throughout the life-course, to enhance the well-being of pre-adolescents. (Eur J Dent 2008;2:153-160)
Keywords: Life-course approach; Dental health; Body height-weight; Self-esteem; Preadolescents; Family-related characteristics